The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1097/prs.0000000000005873
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Emotional Artificial Intelligence in Plastic Surgery

Abstract: Background: The use of social media to discuss topics related to and within plastic surgery has become widespread in recent years; however, it remains unclear how to use this abundance of largely untapped data to propagate educational research in the field of plastic surgery. In this prospective, observational study, the authors aimed to delineate which plastic surgery–related topics evoked a significant emotional response within the study population and to assess the utility of motivational artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“… 16 A similar study by Cognovi Labs and Duke University used supervised ML technology to examine commonly hashtagged words associated with plastic surgery. 24 The authors suggest their results might inform decisions to use the title of aesthetic or cosmetic surgeon and emphasized the potential for such applications to influence marketing strategies and the public perception of plastic surgery. 16 , 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 A similar study by Cognovi Labs and Duke University used supervised ML technology to examine commonly hashtagged words associated with plastic surgery. 24 The authors suggest their results might inform decisions to use the title of aesthetic or cosmetic surgeon and emphasized the potential for such applications to influence marketing strategies and the public perception of plastic surgery. 16 , 24 …”
Section: Discussionmentioning
confidence: 99%
“… 24 The authors suggest their results might inform decisions to use the title of aesthetic or cosmetic surgeon and emphasized the potential for such applications to influence marketing strategies and the public perception of plastic surgery. 16 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used algorithms were supervised machine learning (n = 11, 25%) 29 31 , 33 , 34 , 47 , 53 , 54 , 58 , 59 , 65 and artificial neural networks (n = 11, 25%). 36 , 40 , 42 , 43 , 50 , 57 , 60 64 Other algorithms used were convolutional neural networks (n = 8, 19%), 25 , 27 , 28 , 37 , 38 , 39 , 49 , 56 unsupervised machine learning (n = 4, 9%), 41 , 45 , 55 , 68 natural language processing (n = 4, 9%), 34 , 48 , 67 , 68 generative adversarial networks (n = 2, 5%), 17 , 26 computer vision (n = 2, 5%), 32 , 52 and combinations of models (combo; n = 2, 5%). 43 , 44 Input features were typically comprised of raw and preprocessed variables, such as subject characteristics (age, lapse time, comorbidities, vital signs, and laboratory values, anatomical and wound measurements, tissue reflectance spectrum), clinical images (facial photography, CT images, angiography, photoplethysmography, dermatoscopy, 3D cephalograms), surgical factors (surgical approach, intraoperative interactions with equipment), and synthetic or experimentally derived metrics (external muscle stimulation pulse widths, frequently asked questions).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, only three studies used prospective data, 48 , 55 , 58 and five reported an area under the curve (AUC). 25 , 35 , 40 , 58 , 62 None of the papers were deficient in all nine quality criteria examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation